A population-level metric for gambling-related harm. Issue 2 (4th May 2017) - Browne, Matthew; Greer, Nancy; Rawat, Vijay; Rockloff, Matthew
Abstract: Prior estimates of the population-level impact of gambling have relied on economic costings. Recent work has derived disability weights for the Problem Gambling Severity Index, which measure per-person impact of gambling on quality of life on a scale of zero to one. This provided scope for the present study to calculate the 'burden of gambling harm', which captures the aggregate impact of harms arising from gambling on quality of life in a population. Gambling-related harm was associated with 101, 675 years of life lost in Victoria, Australia: approximately two-thirds that of alcohol use and dependence, and major depressive disorder. Problem gamblers suffer more individually (disability weight = .44) compared to those in moderate (.29) and low (.13) risk categories. Nevertheless, moderate and low-risk gamblers account for 85% of population-level harm, due to greater prevalence of these groups. Overall, the scale of gambling-related harm is large relative to other significant health issues, with milder yet non-negligible harm accruing to a relatively broad segment of the gambling population. The article suggests that the tendency to conflate the (typically low) prevalence of problem gambling with total gambling impact is misleading, and argues for a broader population-health based measure.